Animal Spirits and the International Transmission of Business Cycles - Paul De Grauwe; Yuemei Ji (Center for Economic Studies and ifo Institute (CESifo), 2016)
It is well-known that the high synchronization of the business cycles among industrial countries cannot easily be replicated in standard open economy macroeconomic models without assuming that the exogenous shocks hitting these countries are highly correlated. We develop a two-country behavioral macroeconomic model where the synchronization of the business cycle is produced endogenously. The main channel of synchronization occurs through a propagation of “animal spirits”, i.e. waves of optimism and pessimism that become correlated internationally. We find that this propagation occurs with relatively low levels of trade integration. We also study the transmission of demand and supply shocks from one country to the other and find that the size of this transmission also depends on animal spirits. As a result, the size of the transmission depends on the timing of the shock.
Keywords: E10; 330; animal spirits; monetary policy; monetary union; business cycle